Exechia atlantis - Nunes, Rui (2021)
JUSTIFICATION: Exechia atlantis is an endemic species of the Azores (Portugal), that was described from S. Miguel island. This species was collected in a single area of exotic (production) forest, in a site that is currently degraded. From the historical data, this species would have a very small Extent of Occurrence (4 km² ) and Area of Occupancy (4 km² ); and it is possible that this species has declined in the past, as a result of human activity. However, the present situation of this species needs to be assessed, and further research is needed into its population, distribution, threats, ecology and life history. Conservation/restoration of native habitats and humid areas could potentially aid this species conservation. Based upon the lack of recent in data regarding this species population, distribution, threats and ecology, this species is assessed as Data Deficient (DD).